Study of tensor analysing component T21 for the pi-meson photoproduction on the deuteron - Stibunov V. N. Victor Nikolaevich; Barkov L. M.; Gauzshteyn V. V.; Dmitriev V. F.; Loginov A. Yu.; Mishnev S. I.; Nikolenko D. M.; Osipov A. V.; Rachek I. A.; Sidorov A. A.; Toporkov D. K.; Fix A. I.; et al. (2010, 2010)
В фонде НТБ ТПУ отсутствует